Reduction in ochratoxin a occurrence in coffee: from good practices to biocontrol agents - López-Rodríguez, Claudia; Verheecke-Vaessen, Carol; Strub, Caroline; Fontana, Angélique; Schorr-Galindo, Sabine; Medina, Angel (MDPI, 2024)
Ochratoxin A (OTA) is a mycotoxin mainly produced by Aspergillus section Circumdati and section Nigri across the coffee chain. OTA is nephrotoxic and is a threat to human health. This review summarizes current knowledge on how to reduce OTA concentration in coffee from farm to cup. After a brief introduction to the OTA occurrence in coffee, current good management practices are introduced. The core of this review focuses on biocontrol and microbial decontamination by lactic acid bacteria, yeasts and fungi, and their associated enzymes currently reported in the literature. Special attention is given to publications closest to in vivo applications of biocontrol agents and microbial OTA adsorption or degradation agents. Finally, this review provides an opinion on which future techniques to promote within the coffee supply chain.
Keywords: ochratoxin A; toxigenic fungi; post-harvest management; lactic acid bacteria; yeasts; biocontrol; biodegradation; detoxification; 3107 Microbiology; 31 Biological Sciences